Health poverty alleviation in China from the perspective of historical institutionalism: policy changes and driving factors - Xu, Li; You, Xiaojian; Cui, Yinan; You, Jiali (Frontiers in Public Health, 2024)
Health poverty alleviation is an effective tool to improve the quality of life and development conditions of poor people. It is also an important means of realizing the "Healthy China" initiative.Since the reform and opening up, changes in health poverty alleviation have been divided into the following three periods: the early stage of health poverty alleviation , the exploration period (2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012) and the development period (2013 to present). This clarifies the regional practice of the government's health poverty alleviation policy and identifies the institutional elements of evolution. It also demonstrates that institutional factors, path dependence and subject interaction combine to bring about change in the health poverty alleviation policies. However, problems such as social forces participating in health poverty alleviation and the construction of medical and health personnel in poor areas loom large.